WAYS OF ENSURING FOREIGN LABOR MIGRATION FLOWS IN THE REGION (Marketing Journal, 2025)
This article discusses the features, existing opportunities and implementation issues of ensuring external labor migration flows in the region. Also, conclusions and proposals are developed on ensuring external labor migration flows in the region.
Keywords: region; labor; external labor; migration; flow; factor